Cool colour impact on thermal comfort and sensation / Zaim Ahnaf Abd Rahim - Abd Rahim, Zaim Ahnaf (2022)
It has become a worldwide priority to achieve indoor thermal comfort and sensation through creative and energy-sufficient ways as climate change becoming a growing concern. Colour as one of the important characteristics in indoor spaces has been lacked for its consideration towards thermal comfort and sensation due the inadequate evidence and investigation. Therefore, this study aims to determine the impact of cool colour thermal comfort and sensation. 3D simulation model of walkthrough in a reading room was used as the mediator to test the impact of cool colour hue on thermal comfort and sensation. 30 subjects – 19 males and 11 females – from different group of age participate in this study. Subjects had been visualized with a reading room simulation model with 5 different wall colours (white, blue-green, green, purple-blue and purple). For each simulation model, subjects were surveyed regarding their thermal comfort and sensation as well as body test of heart and blood pressure. Descriptive analysis found no difference on thermal comfort and sensation between white coloured wall and cool coloured wall. Participants felt cool and comfortable regardless the simulation conducted in warm environment.